2020
DOI: 10.1001/jamapsychiatry.2020.0527
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Associations Between Childhood Psychopathology and Adult Depression and Associated Traits in 42 998 Individuals

Abstract: IMPORTANCE Adult mood disorders are often preceded by behavioral and emotional problems in childhood. It is yet unclear what explains the associations between childhood psychopathology and adult traits. OBJECTIVE To investigate whether genetic risk for adult mood disorders and associated traits is associated with childhood disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
52
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 80 publications
11
52
2
Order By: Relevance
“…Strong genetic correlations (|rg| > 0.7) with adult depression, anxiety, neuroticism, and the wellbeing spectrum were of note, and suggest a substantial shared genetic etiology between childhood internalising symptoms and adult internalising disorders and related traits, that has also been observed in previous studies (44)(45)(46). However, the observed correlations with adult internalising disorders were partial rather than complete, indicating that from a developmental perspective, childhood and adolescent internalising symptoms are not genetically identical to adult depression or anxiety.…”
Section: Discussionsupporting
confidence: 78%
“…Strong genetic correlations (|rg| > 0.7) with adult depression, anxiety, neuroticism, and the wellbeing spectrum were of note, and suggest a substantial shared genetic etiology between childhood internalising symptoms and adult internalising disorders and related traits, that has also been observed in previous studies (44)(45)(46). However, the observed correlations with adult internalising disorders were partial rather than complete, indicating that from a developmental perspective, childhood and adolescent internalising symptoms are not genetically identical to adult depression or anxiety.…”
Section: Discussionsupporting
confidence: 78%
“…PRS have been used to assess the impact of genetic contributions on depressive phenotypes at various ages. For example, PRS of MDD have recently been associated with self-or maternal-reported childhood psychopathologies, such as internalizing symptoms from 7 to 16 (Akingbuwa et al, 2020), as well as self-reported adolescent depressive symptom trajectories from ages 10 to 24 (Kwong et al, 2019;Rice et al, 2018). Although these studies have provided important new insights into All rights reserved.…”
Section: Most Of Them Have Characterized Between Three and Six Primarmentioning
confidence: 99%
“…https://doi.org/10.1101/2020.03.02.19007088 doi: medRxiv preprint 6 the genetic underpinnings of depression, they collectively have two main limitations. First, most have focused on narrow ages range, with only one study including children younger than 10 years old (Akingbuwa et al, 2020). Thus, there has been limited attention to the earliest manifestations of depressive symptoms, which is a shortcoming as some symptoms can emerge as early as preschool (Whalen et al, 2017).…”
Section: Most Of Them Have Characterized Between Three and Six Primarmentioning
confidence: 99%
“…However, despite substantial twin heritability (a mean of 60%; Cheesman et al, 2017), GPS heritabilities are modest for childhood behaviour problems such as autism spectrum disorder (2.5%; Grove et al, 2019) and ADHD (3.3%; de Bode et al, 2020). In a recent study, GPS prediction of childhood ADHD symptoms, internalizing and social problems was reported to be much lower for adult-based GPS of major depression (0.2%), neuroticism (0.1%), insomnia (0.05%) and subjective wellbeing (0.06%) (Akingbuwa et al, 2020). A recent GWA study of childhood and adolescence internalizing symptoms predicted 0.4% of the variance in internalizing at age 7 and 0.03% at ages 13-18 (Jami et.…”
mentioning
confidence: 99%
“…To test the hypothesis that the multi-GPS approach will yield greater GPS heritability than the single-GPS approach, we assessed the joint prediction of 15 GPS in penalised regression models with out-of-sample evaluation of prediction accuracy (multi-GPS) (Zou & Hastie, 2005). In addition to GPS for childhood behaviour problems (ADHD; autism spectrum disorder), we included GPS derived from the much larger GWA studies of adult psychiatric disorders such as schizophrenia, bipolar disorder and major depressive disorder and traits such as neuroticism, well-being and risk-taking as they have been shown to predict a variety of childhood phenotypes, including psychopathology (Allegrini et al, 2020b) and behaviour problems (Akingbuwa et al, 2020).…”
mentioning
confidence: 99%